Trajectory-Based Obstacle Avoidance And Pilot Cueing Via 3D Conformal Symbology In Degraded Visual Environments - Esmek, C. C.; Tauro-Padival, R.; Feigh, K. M.; Prasad, J. V. R. (My University, 2025)
Low situational awareness (SA) when operating close to terrain and obstacles significantly increases risk by dramatically reducing reaction times. This study aims to facilitate real-time trajectory adjustments and improve pilot SA without increasing cognitive load by focusing on the specific challenge of maneuvering around obstacles in hostile and degraded visual environments (DVE). This methodology aims to enhance the safety and efficiency of low-altitude rotorcraft operations. This study proposes an outer-loop guidance methodology and decision logic to facilitate a smooth transition between turn, climb, and deceleration maneuvers under appropriate circumstances during flight. Several desktop simulations are performed in the MATLAB/Simulink environment using different pilot models to test the performance in terms of obstacle avoidance and mission completion within the specified time interval. The primary objective of these studies is to lay the groundwork for future pilot-in-the-loop simulations by designing a framework to integrate this guidance method into a simulator, where visual cues are presented as a 3D conformal symbology set using a Heads-Up Display (HUD) to support the 'heads-up, eyes-out' interface philosophy. The proposed 3D conformal symbology set is explained. This preliminary work is intended to enhance the potential effectiveness of the pilot's cueing system in hostile and degraded visual environments once actual testing and implementation are underway.